Factors associated with using penicillins as the first-choice antimicrobial among dentists in Japan: a national cross-sectional study - Ryuji Koizumi; Masahiro Ishikane; Yoshiki Kusama; Shinya Tsuzuki; Yusuke Asai; Yasuyuki Shimada; Chika Tanaka; Akihiro Kaneko; Norio Ohmagari (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract